Residual atherothrombotic burden after primary percutaneous coronary intervention and myocardial reperfusion—An optical frequency domain imaging study. Issue 1 (13th August 2019) - Roule, Vincent; Schwob, Lin; Lemaitre, Adrien; Bignon, Mathieu; Ardouin, Pierre; Sabatier, Rémi; Blanchart, Katrien; Beygui, Farzin
Abstract: Objectives: We aimed to assess the relationship between residual in‐stent atherothrombotic burden (ATB) after primary percutaneous coronary intervention (PCI) measured by optical frequency domain imaging (OFDI) using different measurement methods and myocardial blush grade (MBG). Background: The impact of residual ATB after primary PCI on myocardial reperfusion remains unclear. Methods: We prospectively included 60 ST‐elevation myocardial infarction patients pretreated with aspirin and ticagrelor. OFDI volumetric quantification using planimetry (with intervals every frame or every millimeter) and semiquantitative score were used to determine ATB. Patients were divided into two groups according to final MBG 3 or <3. Results: The mean ATB was 10.08 ± 5.21%. ATB was lower in patients with final MBG 3 compared to those with impaired MBG, regardless of the measurement method (8.15 ± 5.58 vs. 11.77 ± 4.28%; p = .007 for quantification per frame; 7.8 ± 5.19 vs. 11.07 ± 4.07%; p = .009 for quantification per mm and 11.21 ± 11.75 vs. 22.91 ± 17.35; p = .003 for the semiquantitative thrombus score, respectively). Conclusion: Residual post‐stenting ATB remains substantial after primary PCI in STEMI patients, even when pretreated with ticagrelor and aspirin. ATB appears as a significant correlate of suboptimal myocardial reperfusion, a known surrogate of clinical outcome.